Permissive Attitudes to Domestic Violence on Women in Indonesia - Oktriyanto, Oktriyanto; Nugraha, Arga; Puspitasari, Mardiana Dwi; Nasution, Sri Lilestina; Novianafari, Ifa Prasetya (MUWAZAH: Jurnal Kajian Gender, 2021)
Violence against women occurs in almost all countries and has become a global issue that is often reviewed and discussed at various seminars. The United Nations defines violence against women as "Any act of gender-based violence that results in or is likely to cause physical, sexual, or mental damage or suffering to women, including the threat of such actions, the coercion or deprivation of liberty arbitrarily, whether occurring in the public sphere and private life. The purpose of this analysis is to determine the effect of sociodemographic characteristics and women's involvement in decision-making in the household on permissive attitudes towards domestic violence in women. This analysis uses the 2017 Indonesian Demographic and Health Survey (IDHS) data source with the unit of analysis being married women aged 15-49 as many as 35,681 respondents. Data analysis was performed descriptively and inferentially. The logistic regression multivariate test was used to analyze the influence of sociodemographic characteristics and women's involvement in decision making on the permissive attitude of domestic violence to women. The results of the analysis found that several variables influence permissive attitudes on domestic violence in women, namely: the role of women in decision making, age, number of children still alive, education level, access to the internet, wealth quintile, and location of residence. While work status does not significantly influence permissiveness towards domestic violence. Proactive socialization, comprehensive policy, and coordination across related sectors on an ongoing basis are expected to reduce domestic violence in the community.